Shared disbelief and shared belief: Belief and disbelief as drivers of interpersonal neural synchronization during narrative processing - Gabriel Braun; Yaara Yeshurun; Einat Shetreet (Proceedings of the National Academy of Sciences, 2025)
Despite living in an era where the mere concept of truth is increasingly contested, the cognitive processes underlying the processing of information we believe or disbelieve remain largely unexplored. In this fMRI study, we investigated how belief modulates narrative processing through belief context—the initial information indicating the speaker’s credibility—and actual belief—the truth value ultimately assigned by the listener. Across two experiments, participants listened to narratives preceded by contexts explicitly stating whether the speaker was lying or telling the truth. Then, after listening to the narratives, they were asked to rate their actual belief. To investigate the effects of (dis)belief on narrative processing, we analyzed neural synchronization using inter-subject-correlation analysis and inter-subject representational similarity analysis. In both experiments, we successfully differentiated (dis)belief contexts by modeling neural synchronization patterns, despite an actual “belief-bias” at the behavioral level. This indicates a unique neural pattern related to each belief context. Furthermore, our results revealed a dissociation between belief and disbelief in both contextual and actual (dis)belief. Per each narrative, belief and disbelief were associated with increased synchrony within the default mode network, but in distinguishable parcels. These findings highlight the influence of (dis)belief on narrative processing at both behavioral and neural levels. Behaviorally, the observed belief-bias supports the notion of belief as a cognitive default. Neurally, we suggest that belief and disbelief can be understood as fostering qualitatively distinct processing or interpretation of the same narrative, which are then reflected in shared neural responses among individuals who hold similar belief states.